Exploring Digital Literacy Among Primary School Teachers: Menjelajahi Literasi Digital di Kalangan Guru Sekolah Dasar - Anggraeni, Ratna Dwi; Wachidah, Kemil (House of Wisdom: Journal on Library and Information Sciences, 2025)
This research aims to determine the digital literacy of teachers at SDN Kandangan, a case study of grade V teachers. The object of this research is grade V teachers at SDN Kandangan. Qualitative research uses the case study method with research objectives directed at collecting data, extracting meaning and gaining understanding from the cases studied. Namely by collecting data by interviewing the teacher concerned based on the instrument created by the researcher and observing the grade V teacher at SD Negeri Kandangan. The data analysis technique used in this research is descriptive narrative. This technique uses the Miles and Huberman model which includes stages of data reduction, data presentation, and drawing conclusions or verification. Highlights: Research focuses on grade V teachers at SDN Kandangan. Data collection through interviews and observations. Analysis using Miles and Huberman's model (data reduction, presentation, and conclusion). Keywords: Digital Literacy, Teacher, Education Technology